Contemporary Parenting Behaviors and Attitude Toward Learning: Basis for Academic Enhancement Program - Gladysma Kate Ruga (Journal of Elementary and Secondary School, 2023)
To address the high percentage of low-performing Filipino learners, as the the Organization for Economic Cooperation and Development (OECD) revealed, the research investigated the relationship between the level of contemporary parenting behaviors and the level of attitude towards learning Grade 7 students and parents. Through this, the Filipino learners' poor academic performance outcomes in PISA 2018 may be addressed by proposing and implementing an effective academic enhancement program. A total of 284 adolescents and parents, selected at random, participated by answering the two adopted standardized questionnaires, and the model was analyzed and evaluated using Mean, Parenting Behaviors and Dimensions Questionnaire and Attitude toward Learning Scale, T-test for independence and Pearson-Product Moment Correlation. The results revealed that emotional warmth, anxious intrusiveness, and democratic discipline were practised more often than punitive, permissive, and autonomy support. Moreover, students showed a favourable attitude toward the nature of learning and expectations from learning. On the other hand, their attitudes toward openness to learning and anxiety about learning were observed to need improvement. In addition, the results showed a significant difference between the assessments of the Grade 7 students and their parents. It was also revealed that there is a significant relationship between contemporary parenting behaviors and attitudes toward learning. An Academic Enhancement Program was developed to address the problems and concerns observed and help the students with their academic endeavours.